Incentivizing Supplemental Nutrition Assistance Program Purchases with Fresh Produce in Corner Stores to Reduce Food Inequity in Underserved Areas of Washington DC (Mary Ann Liebert, 2020)
Purpose: Maintaining a healthy eating pattern plays a key role in ensuring optimal health outcomes, yet, in areas considered ?food deserts? and lower-income neighborhoods where the accessibility of healthy foods and beverages is limited, the pursuit of adequate nutrient intake is rendered cumbersome. This pilot program aims to improve access to healthful foods by supporting corner stores in stocking and promoting the purchase of produce. Methods: DC Central Kitchen's Healthy Corners program in Washington, DC piloted a nutrition incentive model in 17 corner stores that were upgraded to stock an increased variety and quantity of fresh produce. This program, entitled ?5-for-5,? provided a $5 coupon toward the purchase of fresh produce to Supplemental Nutrition Assistance Program (SNAP) shoppers making a qualifying purchase of $5 or more with SNAP benefits. Results: Evaluation based on store owner buy-in and customer intercept surveys indicated overall satisfaction in program offerings with 77% of SNAP shoppers polled indicating an increase in produce consumption as a direct result of the program. Coupon distribution data indicated that in the 5-for-5 program's first year, 76.5% of all 57,989 distributed coupons were redeemed, amounting to $221,770 worth of incentivized fresh produce sales. Conclusion: The results of the incentive program were promising with increases in the amount of produce purchased as a result of the program. Lessons learned concerning the use of a financial incentive to encourage the purchase of produce at corner stores is explored, as well as the feasibility of the corner store as a sustainable venue to increase produce consumption in underserved communities.